A Traffic Engineering Approach to Differentiated Multicast Services over MPLS Networks - Barabas, Toni (Université d'Ottawa / University of Ottawa, 2012)
Currently, a viable solution to provide multicast provision over a multiprotocol label switch with traffic engineering (MPLS-TE) domain is unavailable because of the missing link able to couple multicast traffic distribution with an MPLS-TE enabled network. This is due to the limited or less research investigation that was done in this area. Most of the investigation methods tackle the problem individually such as deploying internet protocol (IP) multicast in a plain network or MPLS domain but without considering a combination of both technologies that is aware of differentiated services requirements. This thesis presents an alternative solution for the multicast differentiated services provision problem over a MPLS-TE enabled network. The approach is exposed and analyzed through a practical solution that was developed within a network simulation environment. The research presented in this thesis orchestrates the already available technologies offered by the multicast protocols suite and differentiated services (DiffServ) aware MPLS-TE that allows applying separately the constraint-based routing and admission control to different classes of services. The novelty and solution of this thesis relies on using MPLS constraint-based routing concepts (e.g.traffic trunks) in order to solve TE issues revealed during multicast traffic distribution.
Keywords: IP multicast; PIM-SSM; QoS; Diff-Serv; MPLS-TE